The Cambridge history of later medieval philosophy - Kretzmann, Norman; Kenny, Anthony; Pinborg, Jan (Cambridge Cambridge University Press, 1982)
This 1982 book is a history of the great age of scholastism from Abelard to the rejection of Aristotelianism in the Renaissance, combining the highest standards of medieval scholarship with a respect for the interests and insights of contemporary philosophers, particularly those working in the analytic tradition. The volume follows on chronologically from The Cambridge History of Later Greek and Early Medieval Philosophy, though it does not continue the histories of Greek and Islamic philosophy but concentrates on the Latin Christian West. Unlike other histories of medieval philosophy that divide the subject matter by individual thinkers, it emphasises the parts of more historical and theological interest. This volume is organised by those topics in which recent philosophy has made the greatest progress.